2020
DOI: 10.13106/jafeb.2020.vol7.no4.163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exchange Rate Shocks, Inward FDI and Import on Export Performance: A Cointegration Analysis

Abstract: The study aims to examine the effects of inward every presence of foreign investment, import, and real exchange rate shocks on export performance in Vietnam. This study employs a time-series sample dataset in the period of 2009 -2018. All data are collected from the General Statistics Office of Ministry of Planning and Investment in Vietnam, World Development Indicator and Ministry of Finance, State Bank of Vietnam. This study employs the Augmented Dickey-Fuller test and the vector error correction model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 19 publications
(31 reference statements)
0
27
0
1
Order By: Relevance
“…As a result, the highest correlation (-0.594) observed is between LLP and INF. Nguyen and Do (2020) argued that multicollinearity existence can be found if correlation coefficient is 0.8 and more. It is accordingly confirmed that there is no absence of multicollinearity in our regression analyses.…”
Section: Regression Methodsmentioning
confidence: 99%
“…As a result, the highest correlation (-0.594) observed is between LLP and INF. Nguyen and Do (2020) argued that multicollinearity existence can be found if correlation coefficient is 0.8 and more. It is accordingly confirmed that there is no absence of multicollinearity in our regression analyses.…”
Section: Regression Methodsmentioning
confidence: 99%
“…A multicollinearity question can arise in the case of a correlation value of 0.8 or greater between two independent variables. That applies to the state of testing for heteroskedasticity (Nguyen & Do, 2020) based on Inflation Factor 10 and under variance (VIF). Table 3 shows the effects of independent variables that do not reach the minimum threshold, and Table 4 states that the VIF coefficient does not surpass the maximum threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, a country's economic transactions with an open economy are reflected in its balance of payments. The exchange rate exists in a close relationship with the balance of payments as well as the with the balance of payments components such as the trade account in the current account (Koivu and García-Herrero, 2007;Nguyen and Do, 2020;Kamran et al, 2020). Numerous studies have given many theoretical frameworks related to trade balance in the world.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Vietnam's economy is growing strongly and integrating deeply into the world economy with the trade balance being improved recently after a long period of deficit, bad debts in the banking system, and instable economic policies including the exchange rate policy (Nguyen and Do, 2020;Dao et al, 2020). In this case, the question "is the current exchange rate suitable?"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation